A stiffness controllable multimodal whisker sensor follicle for texture comparison - Wegiriya,H; Herzig,N; Guaman,SAA; Sadati,H; Nanayakkara,T (IEEE Sensors Journal, 2020)
Mammals like rats, who live in dark burrows, heav-ily depend on tactile perception obtained through the vibrissalsystem to move through gaps and to discriminate textures. Theorganization of a mammalian whisker follicle contains multiplesensory receptors and glands strategically organized to capturetactile sensory stimuli of different frequencies. In this paper, weused a controllable stiffness soft robotic follicle to test the hy-pothesis that the multimodal sensory receptors together with thecontrollable stiffness tissues in the whisker follicle form a physicalstructure to maximize tactile information. In our design, the ringsinus and ringwulst of a biological follicle are represented by alinear actuator connected to a stiffness controllable mechanismin-between two different frequency-dependent data capturingmodules. In this paper, we show for the first time the effectof the interplay between the stiffness and the speed of whiskingon maximizing a difference metric for texture classification.